Bimbingan Karir Terhadap Pemilihan Studi Lanjut Siswa Kelas XII - Istirahayu, Iip; Mayasari, Dian; Fitriyadi, Slamat; Damayanti, Zulita (Jurnal Bimbingan dan Konseling Terapan, 2018)
Selection of further study is a problem that is often experienced by students. The inability to make choices of college, department, academic ability, will cause anxiety and anxiety that will make decisions based on the influence of others such as parents, family, and friends. To assist students in understanding the selection of advanced studies appropriate to their interests and talents, there needs to be a career guidance service. This study aims to determine the magnitude of the influence of career guidance services against the election of advanced study of grade XII students. The method used is quantitative research using SPSS 17.0 on simple linear regression test which is used to know the effect of career guidance service on selection of further study. This study used a sample of 120 students of Class XII who were taken by random sampling at Senior High School in Singkawang city. The results showed that the career guidance service gives influence to the students of class XI in determining the selection of further study. From result of linear regression calculation by using SPSS 17.0 application so big influence is 0.098. the conclusion is that any career guidance services provided, will have a positive effect of 0.098 on the ability of students in choosing further studies. Suggestions for students, in order to follow the existing career guidance services in school so that it can assist in determining the decision selection of further study in accordance with the talents, interests and abilities possessed. For teachers of BK, can maximize career guidance services especially related to advanced studies so that students are able to choose and determine the choice of study of interest and in accordance with the ability possessed. The next researcher, this study is expected to be used as a reference and developed.